240 Research Model of Colostrum Intake to Study Effect of Colostrum Bioactive Factors on Piglets Development. (7th May 2021) - Senn, Lisa K; Suarez-Trujillo, Aridany; Teeple, Kelsey; Casey, Theresa; Stewart, Kara R
Abstract: Swine colostrum intake within the first 24 hours after birth plays a large role in determining survivability, feed efficiency, growth, and fertility. This study tested the effects of feeding three doses of a homogeneous colostrum sample on BW over 24h, RT, immunocrit, and growth through PND7. Three female piglets were selected from eight litters at birth (n = 24 piglets total; n = 3/liter), and bottle-fed 10% (COL10, n = 8), 15% (COL15, n = 8) or 20% (COL20, n = 8) BW colostrum over 24h. Piglet birth weights were similar between treatments (P = 0.838). Piglets were weighed, RT recorded and immunocrit measured at 24h postnatal, then returned to their litter of origin. BW was recorded daily through PND7. At 24h, COL20 had an ADG of 136.3g, COL15 86.3g, and COL10 8.8g, and an average RT of 39.30⁰C, 38.84⁰C and 38.81⁰C respectively. Immunocrit levels varied from 0.028, 0.024 and 0.017 at 24h. SAS MIXED procedure was used to perform statistical analysis. Post-hoc analysis was performed using Tukey's test. Colostrum dose had an effect on 24h weight gain (P < 0.001), RT (P = 0.007), immunocrit (P = 0.026), and growth through PND7 (P < 0.05). Treatment, day and interaction were determined as main effects of BW and ADG through PND7. Post-hoc analysis showed COL20 had higher ADG (136.3±54.8g), RT (39.30±0.11°C) and immunocrit (0.028±0.010) at 24h than COL10 (ADG 8.8±24.9g, RT 38.81±0.26°C, immunocrit 0.017±0.004). COL15 ADG (86.3±85.2g) differed from COL10 (P < 0.001), and RT (38.84±0.45) differed from COL20 (P = 0.017). There was no statistical difference in ADG between groups through PND7 (P = 0.874). One piglet within each treatment was crushed before PND7. This model permits controlled studies intended to understand the level of 24h colostrum intake on piglet growth and development using standardized, homogenous colostrum doses.